The clinical characteristics and prognosis of patients with primary plasma cell leukemia (pPCL) according to the new IMWG definition criteria. Issue 12 (15th October 2022) - Yan, Wenqiang; Fan, Huishou; Xu, Jingyu; Liu, Jiahui; Li, Lingna; Du, Chenxing; Deng, Shuhui; Sui, Weiwei; Hao, Mu; Yi, Shuhua; Zou, Dehui; Qiu, Lugui; et al.
Abstract: Recently, the definition of primary plasma cell leukemia (pPCL) has been revised as the presence of circulating plasma cells (CPCs) ≥5% in peripheral blood smear. Consequently, the clinical features and prognosis of this aggressive disease can be truly identified by the larger patient cohort. Herein, we identified 158 new-defined pPCL patients among 2, 266 MM patients (7.0%), and such prevalence doubled the previous estimate. Our study firstly provided solid support for the application of the new definition. We also found that cytopenias and adverse prognostic biomarkers were more common in new-defined pPCL compared with MM ( p < 0.05). Besides, the patients receiving proteasome inhibitors based regimen in combination with stem cell transplantation could experience a considerable survival benefit. Strikingly, we showed that the presence of conventional high-risk cytogenetic abnormalities in pPCL didn't exert a great prognostic effect like MM, while elevated LDH reflecting tumor cells proliferation rate was the only independent predictor.